2017
DOI: 10.1103/physrevlett.118.094501
|View full text |Cite
|
Sign up to set email alerts
|

Condensation on Highly Superheated Surfaces: Unstable Thin Films in a Wickless Heat Pipe

Abstract: A wickless heat pipe was operated on the International Space Station to provide a better understanding of how the microgravity environment might alter the physical and interfacial forces driving evaporation and condensation. Traditional heat pipes are divided into three zones: evaporation at the heated end, condensation at the cooled end, and intermediate/adiabatic in between. The microgravity experiments reported herein show the situation may be dramatically more complicated. Beyond a threshold heat input, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…When the temperature gradient is applied against the spreading direction, there is only a slight decrease in the rectification coefficient, suggesting the stability of the directional transport even when subject to an externally applied temperature field. Such a capability holds many potential applications, such as in heat pipes ( 47 ). Finally, the directional droplet transport applies to any liquid including low–surface tension liquid, such as hexane (~18.4 mN/m), and high-viscosity liquid, such as ethylene glycol (~16.06 mPa·s) ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…When the temperature gradient is applied against the spreading direction, there is only a slight decrease in the rectification coefficient, suggesting the stability of the directional transport even when subject to an externally applied temperature field. Such a capability holds many potential applications, such as in heat pipes ( 47 ). Finally, the directional droplet transport applies to any liquid including low–surface tension liquid, such as hexane (~18.4 mN/m), and high-viscosity liquid, such as ethylene glycol (~16.06 mPa·s) ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The instability leads to dewetting of the film and formation of drops. Both liquid and solid-state dewetting at the nano-scale are relevant in many phenomena (Blossey 2012;Gentili et al 2012;Thompson 2012;Mukherjee & Sharma 2015; Pierre-Louis 2016) such as pumping liquids using nanowires (Huang et al 2013), patterning via self-assembly (Gau et al 1999;Higgins & Jones 2000;Lopes & Jaeger 2001;Huang et al 2005;Segalman 2005;van Hameren et al 2006;Pokroy et al 2009;Fowlkes et al 2011;Han & Lin 2012;Thiele 2014;Wu et al 2015;Kong et al 2015Kong et al , 2016, synthesis of core-shell nanoparticle arrays (McKeown et al 2015), droplet generation (Yamamoto et al 2015;Keiser et al 2017), needle growth (Yu et al 2013), understanding slip and rheology of nanometric films (Herminghaus et al 2002;Fetzer et al 2005Fetzer et al , 2007aBäumchen & Jacobs 2010;Bäumchen et al 2012;Bäumchen et al 2014;McGraw et al 2014), tear film dynamics (Braun 2012), film flow in heat pipes (Kundan et al 2017), Rayleigh-Plateau instability of nano-wires or liquids in nano-channels (Molares et al 2004;Chen et al 2007), or stability of bubbles/drops in micro/nano-channels (Huerre et al 2015;Hammoud et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Here evaporation removes large amount of heat and subsequently reduces the local temperature due to its endothermic attribute. However, recent studies have found unexpected condensation rather than evaporation in the heated region of heat pipe under superheated conditions [13]. This deviates from the conventional knowledge and may cause severe reliability issues.…”
Section: Extended Abstractmentioning
confidence: 85%